Penguasaan Kosakata Anak Penyandang Autis Childhood Disintegrative Disorder (CDD) melalui Penggunaan Media Kartu Kata di Kabupaten Bantaeng - Alfiah Ashilah; Idawati Idawati; Abdul Haliq (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2026)
This study aims to describe the vocabulary mastery and types of responses of a child with Childhood Disintegrative Disorder (CDD) through the use of word card media in Bantaeng Regency. The study employs a descriptive qualitative method, focusing on a single subject diagnosed with Childhood Disintegrative Disorder (CDD). Data were collected through observation, interviews, and documentation, and subsequently analyzed qualitatively. The results indicate that the subject was able to acquire six new vocabulary words through the use of word card media and demonstrated four forms of responses verbal, nonverbal, repetitive, and creative during the learning process. These findings suggest that word card media can support vocabulary acquisition while simultaneously fostering various forms of communicative responses in a child with Childhood Disintegrative Disorder (CDD).